INSTITUTIONAL PRACTICES AND EMPLOYEES’ WORK ENGAGEMENT: AN INTEGRATIVE APPROACH TO UNLOCKING THE FUTURE OF UNIVERSITIES’ EMPLOYEES IN NIGERIA - OKEBIORUN, JANET OMOJOLA; ZACCHAEUS, KOFOWOROLA. B.; AMUSA, DARE RILWAN (Sokoto Educational Review, 2025)
Building the capacity of higher education employees is essential for achieving quality academic output and student success. Educational institutions, therefore, must regularly implement quality capacity-building programs. This study examines the relationship between institutional practices and employee work engagement. A descriptive survey research design was used. A sample of 190 lecturers was purposively selected from the 2,339 lecturers at the University of Lagos (UNILAG), Akoka-Yaba, Nigeria. The researchers developed and used a questionnaire entitled the “Institutional Practice and Employees Work Engagement Questionnaire” (IPEWEQ), which had a correlation coefficient of 0.74. Pearson’s Product Moment Correlation (PPMC) was used to test the null hypothesis at a 0.05 level of significance. The findings revealed that institutional practices, such as a supportive leadership style, collaboration, and a supportive work environment, significantly boost employee work engagement in Nigerian universities. The results further revealed a significant relationship between manpower training and development and employee work engagement at UNILAG. The study concludes that employees must have a supportive environment, job resources, support, and a conducive work environment to foster work engagement. Based on these findings, it is recommended that employees be exposed to various capacity-building programs that will develop and strengthen their skills, instincts, and teaching abilities. DOI: https://doie.org/10.0225/SER.2025626526